Qualitative Research into Reading in English as a Foreign Language in Indonesia – Quo Vadis? - Harits Masduqi; Fatimah Fatimah; Arif Subiyanto (Indonesian TESOL Journal, 2021)
Reading is a multidimensional, intellectual activity, which requires specific skills and strategies. Indonesian researchers have conducted research addressing various issues in reading in the domain of English as a Foreign Language/EFL. This article reviews the current development of theories and models of EFL reading and qualitative research into EFL reading in Indonesia. Through discussion of theoretical and practical perspectives, it appears that EFL reading researchers and teachers in Indonesia are interested in promoting and conducting studies not only on the effectiveness of intensive reading, but also of extensive reading in their academic institutions. In this way, their students will have sufficient opportunities to gain competence in both types of reading, and will develop the capability of using their knowledge of English to capitalise on the advancement of science and technology in the global world.